TRANSFORMATION OF SAUDI ARABIAN EDUCATION IN THE FRAMEWORK OF VISION 2030 - Maulana, Rizka Husnu; Badrudin, Badrudin; Erihadiana, Mohamad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research discusses the transformation of education in Saudi Arabia as part of Vision 2030, a strategic initiative to reduce the country's dependence on oil, diversify the economy, and develop the social sector, including education. This transformation includes curriculum reforms, education system modernization, teacher quality improvement, and technology adoption to support learning. The research uses a qualitative approach with relevant literature and policy analysis to understand the steps taken by the Saudi government in creating an inclusive and market-oriented education system. The research findings indicate that educational reforms are key to building competitive human resources, promoting innovation, and strengthening national identity by moderate Islamic principles. However, challenges such as cultural resistance, gender disparities, and the need for adequate infrastructure continue to be obstacles to achieving the goals of Vision 2030. This study concludes that the success of educational transformation requires collaboration between the government, private sector, and society to ensure the sustainability and relevance of reforms in supporting Saudi Arabia's long-term development.